Hormonal changes and follicular activity after treatment with intravaginal progesterone-releasing devices in llamas - Cavilla, María Verónica (2016)
Plasma progesterone (P4) concentrations and follicular activity after administration of different P4 doses were evaluated in 33 adult female llamas treated with intravaginal devices. In Study 1, a group of llamas (n = 10) was treated with an intravaginal device (IVD) containing 160 (n = 5) or 780 mg of P4 (n = 5). Based on the results from the first study, in Study 2, females with follicles at different stages of development were treated with the IVD containing 780 mg of P4 (n = 21) or remain untreated (control; n = 12) to evaluate the effect of P4 on follicular activity. In Study 1, the IVD containing 160 mg of P4 induced follicular turnover in 60% of females while the remaining 40% of llamas developed persistent follicles. Thus, this device controlled follicular activity in llamas, although it promotes the persistence of follicles present at start of treatment. Conversely, in both studies, the IVD containing 780 mg of P4 suppressed follicular development and hasten the emergence of a new follicular wave in all females regardless of the follicular phase at insertion. Additionally, in Study 2, this device effectively concentrated the appearance of follicles with ovulatory diameter at a definite time after treatment in comparison with control animals. In conclusion, treatment with an IVD containing 780 mg of P4 would be considered for the control of follicular activity in llamas as it ensures the presence of a young follicle with ovulatory diameter by day 6 after the end of treatment in all females.